Implementasi Algoritma AES-256 dalam Enkripsi Pengamanan Data pada PT Kallista Prima - Rifaldi Mahsyaf Azmi; Ali Ikhwan (Universitas Methodist Indonesia, 2026)
This study aims to implement the Advanced Encryption Standard (AES-256) algorithm to secure pharmaceutical product pricing data within a product management system, using the AB-VAS K – TABLET product as a case study. The background of this research is based on the importance of protecting pricing data—namely HNA, HNA+PPN, and HET—from risks of manipulation and unauthorized access in information systems. The method used includes system design, encryption and decryption processes using AES-256 with a 256-bit key length and 14 transformation rounds, as well as testing data integrity and sensitivity through the avalanche effect test. The results show that all pricing data were successfully transformed into ciphertext with no recognizable pattern and could be restored identically through the decryption process. The testing also demonstrated that a small change in plaintext produced a significant change in the resulting ciphertext, thereby increasing the security level of the system. With a key complexity of 2²⁵⁶, the implementation of AES-256 is considered effective in maintaining the confidentiality and integrity of pricing data and is suitable for application in pharmaceutical product management information systems.